Altitude-mediated soil microbe-nutrient dynamics shape medicinal properties of Angelica sinensis - Gong, Xiao-Fang; Khan, Wasim; Yang, Ling; Chen, Yu-Kun; Chen, Juan; Zhang, Ling; Zhang, Yong; Zhu, Ying; Wang, Zhi-Ye; Zhang, Bing-Lin; Xue, Lin-Gui (Frontiers in Plant Science, 2026)
BackgroundRhizosphere microorganisms play a critical role in plant growth and medicinal quality, yet their altitudinal patterns and interactions with soil nutrients and bioactive compounds in Angelica sinensis (A. sinensis) remain poorly understood.MethodsUsing Illumina MiSeq sequencing, we analyzed bacterial, fungal, arbuscular mycorrhizal (AM) fungal, and archaeal diversity across an altitudinal gradient, alongside soil physicochemical characteristics and bioactive components.ResultsAs cultivation elevation increased, bacterial and fungal diversity initially increased significantly and then stabilized (p < 0.05). In contrast, AM fungal and archaeal communities remained relatively stable. Bacterial communities varied significantly across altitudes (stress < 0.1, p = 0.001), as did soil nutrients and enzyme activities (p < 0.05). Bioactive components, except for ferulic acid, varied significantly with altitude. Redundancy analysis (RDA) confirmed that altitude and soil factors are key drivers of microbial community assembly. Mantel tests and structural equation modeling (SEM) demonstrated significant correlations between soil properties, microbial diversity, and medicinal properties of A. sinensis (p < 0.05).ConclusionThe mid-to high elevation zone (2520–2717 m) was identified as optimal for both yield and bioactive compound accumulation. These findings deepen the understanding of how microbes adapt to different altitudes in medicinal plants and offer a framework for precise cultivation of A. sinensis, thereby supporting the high-altitude symbiosis theory.